Üçüncü Mertebeden Bir Akışkanın, Biri Hareketli Kesişen İki Plaka Arasındaki Akışı - Barış, Serdar; Bilgiç, Boğaç (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010)
The problem dealing with the two dimensional steady and slow flow ofa third grade fluid between intersecting planes, one of which is fıxed and the other moving, has been analysed. Using a truncated series expansion giyen by Strauss [l] for the stream function, the goveming equations of the problem are reduced to linear ordinary differential equations. These equations have been solved analytically subject to the relevant boundary conditions. The effects of the non-Newtonian parameters on the flow pattern are carefully delineated. There is, unlike the case of Newtonian fluid, a secondary flow near the corner.

Bu problem, üçüncü mertebeden bir akışkanın, Şri sabit diğeri hareketli olan kesişen iki düzlem arasındaki, iki boyutlu daimi akışının analizi ile ilgilidir. Strauss [l] tarafından verilen seri açılımları kullanılarak, problemi yöneten denklemler, lineer adi diferansiyel denklemlere indirgenmiştir. Bu denklemler ilgili sınır koşulları altında analitik olarak çözülmüştür. Non-newtonian parametrelerin akış üzerindeki etkisi dikkatlice incelenmiştir. Newtonian akışkandan farklı olarak, köşe noktası civarında sirkülasyon halkalarının oluştuğu görülmüştür.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2010

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010